Iranian superwomen's career experiences: a qualitative study - Nosrati Beigzadeh, Maryam (BMC Womens Health, 2021)
BACKGROUND: Superwoman refers to the identity of a woman who performs several important roles simultaneously and full-time, such as being a wife, mother, and homemaker while holding a job. This study aims to examine the career experiences of Iranian superwomen who maintained their mental health while holding multiple roles. METHODS: Data for this qualitative study were collected via semi-structured interview and analyzed using conventional content analysis. The study participants were 12 multi-role women from different occupations in Tabriz, North West of Iran selected through purposive and theoretical sampling. The women’s mental health status was assessed using Mental Health Continuum-Short Form questionnaire before participating in the research. RESULTS: The results were classified into three main categories. The first category included Underlying Factors of Job Experience with six subcategories, including Limited job opportunities for women, Educational context (mindset shaped in the parental home), Commitment or freedom in obtaining a job and its continuation, Personality traits, and Non-cognitive skills (emotional intelligence and spiritual intelligence); the second category included the adopted strategies to solve career problems with two subcategories: effective strategies, including the benefits of having a mindset of abundance and having a vision and strategic planning, and ineffective strategies, including the benefits of having a mindset of scarcity; and the third category included Perceived Consequences of employment with two subcategories: psychological consequences and social consequences, with both subcategories including some positive and negative further subcategories. Moreover, a conceptual relationship between the main categories and the subcategories was evident. CONCLUSIONS: The content obtained not only supports the findings about the experiences of multi-role women in cultures outside Iran, but also points to the unique aspects of Iranian superwomen's life experiences and narratives. The findings of this study can help us perceive the real career experiences from the perspective of Iranian professional women with multiple roles. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12905-021-01369-3.